Pengembangan Sistem Usaha Pertanian Berkelanjutan - Made Oka Adnyana (Forum penelitian Agro Ekonomi, 2001)
EnglishAgricultural sustainability is still a debatable concept since there is no standard criteria that suitable for agriculture development. Various studies have been conducted regarding the concept but it's just limited to evaluation on the existing agricultural activities. Nevertheless, the issue then is whether the present capital intensive agriculture and heavy imported input is a sustainable agricultural system?. Agricultural development with agribusiness system approach is then believed as one of alternatives that can enhance agricultural development in Indonesia. In respond to this issue, various action research and assessment on agribusiness system of priority commodities have been conducted since 1995. Great variability of research results were found in relation to various factors such as: (1) Economic of scale, (2) Appropriate technology that suitable to the assessment objectives, (3) Characteristics of the agribusiness system, (4) Criteria of success of the assessment, and (5) Management of agribusiness system develompnet. This paper discussed the future outlook of agribusiness development as sustainability approach in agricultural development. IndonesianPertanian terlanjutkan masih merupakan konsep yang terus diperdebatkan selama belum ada kriteria yang baku sesuai dengan dinamika pembangunan pertanian. Telah banyak studi dilakukan tetapi masih terbatas pada evaluasi kegiatan pertanian yang sedang berjalan. Pertanyaan yang kemudian sering muncul, apakah pertanian yang padat modal dan sarana produksi sarat dengan bahan baku impor dapat terlanjutkan? Pendekatan sistem usaha pertanian, kemudian dipercaya dapat mendorong keberlanjutan pembangunan pertanian. Sehubungan dengan pendekatan tersebut, berbagai pengkajian tentang sistem usaha pertanian komoditas telah di lakukan sejak tahun 1995. Namun hasil dari pengkajian tersebut sangat beragam yang terkait dengan berbagai aspek seperti : (1) Skala ekonomi, (2) Teknologi yang tepat guna  dan sesuai dengan sasaran pengkajian, (3) karakteristik suatu SUP, (4) Kriteria keberhasilan dan (5) manajemen pengembangan SUP. Tulisan ini mencoba mengajukan  konsep tentang pendekatan SUP dalam pembangunan pertanian yang berkelanjutan.